Analisis Gaya Kepemimpinan Menejer terhadap Kinerja Karyawan di KSU Kencana Makmur Cabang Laren - Uhdaul Ummah; R. Zainul Musthofa Musthofa (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2020)
Analysis of Manager's Leadership Style on Employee Performance at KSU Kencana Makmur Laren branch. A leader must also understand about the important strengths contained in his subordinates, each subordinate has different needs, desires and levels of expertise. Thus, a leader can apply all organizational regulations and policies and carry out his duties and responsibilities appropriately, so that later a leader is able to build and improve the performance of his employees to be more effective. Prosperous Laren branch. This research is included in the category of qualitative research, namely research that is more concerned with the interpretation of the data found in the field and carried out in natural conditions (natural setting). Observation is collecting data by observing the activities being observed to obtain the required data. While the interview is a data collection technique by having direct conversations with data sources to obtain the necessary information.